Management of Green Open Space (RTH) in Kendari to Reduce Air Pollution - Indriyani, Lies Indriyani; Sabaruddin, Laode; Rianse, Rianse; Baco, La (European Journal of Sustainable Development, 2016)
The existence of green open space (RTH) is very important in any urban area so that the government issued a policy to regulate the presence of green open space. Based on Law No. 26 Year 2007 on Spatial Planning, which then poured in Local Regulation in Kendari No. 10 of 2011 on the Management of green open space, its requiring green open space at least 30% of the area of the city, while the proportion of green open space public at least 20% and private green open space 10% of the area of the city. Along with a number of city dwellers is increasing, natural resources and environment in the city more and more utilized. This resulted in forest resources more widely utilized and the rate of decline RTH getting faster and the increased activity of urban communities that use fossil fuels leads to high air pollution. This study aims to (1) evaluate the suitability of tree species making up RTH, and (2) make referrals election suitability of tree species that have a growing and effective in controlling air pollution. This study uses survey and identification to determine the constituent tree species. Rate suitability of tree species based site and literature. The results showed that the tree species in Kendari city RTH Region consists of 51 species, 33 species of which in accordance with the requirements of silvicultural, management and aesthetics, while there are 18 species of trees that were considered suitable place to grow and be effective in controlling air pollution. Keywords: green open space, the selection of tree species, air pollution